2016
DOI: 10.1111/nhs.12304
|View full text |Cite
|
Sign up to set email alerts
|

Genetic education, knowledge and experiences between nurses and physicians in primary care in Brazil: A cross‐sectional study

Abstract: Recent advances in genomics and related technologies have the potential to improve health care throughout the world. In this cross-sectional study, we examine genetics education, knowledge, and genetics-related experiences among the nurses and physicians who provide primary care in a Brazilian city. Fifty-four healthcare professionals from family health units participated in the study (response rate: 90%). Data were collected using a structured 36-item questionnaire divided into five axes: sociodemographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 60 publications
1
33
0
6
Order By: Relevance
“…The main objectives of this recent policy are to reduce mortality, to contribute to the reduction of morbidity and of secondary manifestations, and to improve people's quality of life, through actions of promotion, prevention, early detection, timely treatment, reduction of disability and palliative care. 5,11,10 The city of the present study, located in the northern region of Rio Grande do Sul, does not have specialized care in the area of Genetics. Therefore, families of people with GD had to travel long distances to the state capital, where the referral centers in genetics are commonly located.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The main objectives of this recent policy are to reduce mortality, to contribute to the reduction of morbidity and of secondary manifestations, and to improve people's quality of life, through actions of promotion, prevention, early detection, timely treatment, reduction of disability and palliative care. 5,11,10 The city of the present study, located in the northern region of Rio Grande do Sul, does not have specialized care in the area of Genetics. Therefore, families of people with GD had to travel long distances to the state capital, where the referral centers in genetics are commonly located.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, this policy was intended to be incorporated and implemented by SUS at all levels of care, articulating the primary care network with prevention and identification of cases to be referred to specialized care. 2,[7][8][9][10] Above all, this Policy had the purpose of structuring, within the SUS, a regionalized and hierarchical system that would provide comprehensive care in clinical genetics and improve access to specialized services.…”
Section: Introductionmentioning
confidence: 99%
“…Research evaluating nurses' knowledge and skills in genetics‐based health care in different settings and countries has indicated that although nurses of various expertise recognize the importance of genetics in their profession, they lack sufficient confidence in their knowledge and skills to provide appropriate care to individuals who could benefit from genetic services (Terzioğlu & Dinç ; Tomatir et al ; Godino et al ; Saligan & Rivera ; Seven et al ; Lopes‐Júnior et al ). Other studies have evaluated the genetics knowledge of midwives or both midwives and nurses (Goedert et al ; Godino et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work indicates that nurses from many countries feel unprepared to deliver health care to patients who are at risk themselves of a genetic condition, or whose offspring are at risk (Lopes‐Júnior et al, ; Seven, Eroglu, Akyüz, & Ingvoldstad, ; Sriarporn et al, ). Despite attempts to draw nurses into the sphere of genetic and genomic health care through the establishment of relevant competences (Skirton et al, ), a systematic review focused on specific nursing genetic competences indicated that, in fact, nurses did not have the appropriate knowledge and skills to identify patients at increased genetic risk, and act to ensure they were assessed and managed appropriately (Skirton, O'Connor, & Humphreys, ).…”
mentioning
confidence: 99%